2008
DOI: 10.1007/s10812-009-9124-z
|View full text |Cite
|
Sign up to set email alerts
|

Spectral and kinetic characteristics of CdI2 and CdI2:Pb scintillators

Abstract: We have studied the effect of lead dopant on the optical absorption, photoluminescence, and x-ray luminescence spectra, and the scintillation characteristics of CdI 2 at room temperature. The crystals for the study were grown by the Stockbarger-Bridgman method. Activation of CdI 2 from the melt by the compound PbI 2 leads to the appearance in the absorption spectra in the near-edge region of an activator band at 395-405 nm, which is interpreted as an A band connected with electronic transitions from the 1 S 0 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Heterogeneous solid solutions of Pb1-xCdxI2 are characterized by intensive photo-and Xluminescence at room temperature and high radiation resistance, while it opens up a possibility of using these materials for the production of high efficient rapid-action non-cooled scintillation detectors of X-and γradiation [1,2]. In [3], the possibility of using CdI2 crystals with an optimal impurity concentration of Pb ~ 1.0 mol.% as a scintillator for the registration of α-particles was shown. Studies of PbI2 nanostructures with a Cd content of up to 7.5 % have shown that they are a promising material for optoelectronic devices and ionizing radiation detectors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heterogeneous solid solutions of Pb1-xCdxI2 are characterized by intensive photo-and Xluminescence at room temperature and high radiation resistance, while it opens up a possibility of using these materials for the production of high efficient rapid-action non-cooled scintillation detectors of X-and γradiation [1,2]. In [3], the possibility of using CdI2 crystals with an optimal impurity concentration of Pb ~ 1.0 mol.% as a scintillator for the registration of α-particles was shown. Studies of PbI2 nanostructures with a Cd content of up to 7.5 % have shown that they are a promising material for optoelectronic devices and ionizing radiation detectors.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the published works are devoted to the study of the properties of Pb1-xCdxI2 solid solutions grown from melt the Bridgman-Stockbarger technique [1,3] and grown from solutions [4]. The growth of Pb1-xCdxI2 crystals from the vapour phase and their properties have been insufficiently studied.…”
Section: Introductionmentioning
confidence: 99%
“…5 The proposed concept relies on strain-mediated magnetoelectric coupling by combining the inverse piezoelectric and the magnetostrictive effect: the direction of the magnetization of a ferromagnetic particle can thus be controlled by a bias voltage applied across piezoelectric leads supporting the particles. 5 The proposed concept relies on strain-mediated magnetoelectric coupling by combining the inverse piezoelectric and the magnetostrictive effect: the direction of the magnetization of a ferromagnetic particle can thus be controlled by a bias voltage applied across piezoelectric leads supporting the particles.…”
Section: Introductionmentioning
confidence: 99%
“…Pulsed scintillation of an unactivated crystal at room temperature showed a fast (τ 1 ≈ 4 nsec) and slow (τ 2 = 10-76 nsec) stage of emission decay [9]. The fraction of the fast component was ~98%.…”
mentioning
confidence: 98%
“…The luminescence intensity increases and the maximum shifts to the range 540-560 nm as the temperature is lowered to 85 K. Activation of CdI 2 with a homologous anionic dopant of Cl or Br has little effect on the light yield and spectral parameters of CdI 2 at low or high temperature [2]. Doping CdI 2 with Pb 2+ , Sn 2+ , Eu 2+ , Mn 2+ , Cu + , and Ag + does modify the spectral properties of the compound and produces effective luminophores [2][3][4][5][6][7][8][9] and photochromic materials [10].…”
mentioning
confidence: 99%